"MARKETING STRATEGY AS AN EFFORT TO MAINTAIN THE SUSTAINABILITY OF THE COMPANYA THROUGHT PRODUCT QUALITY, PRICE, AND BRAND IMAGE” - Pratminingsih, Sri Astuti; H, Ahmad Edward Rommel; Rahmawan, Fajar (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research was conducted to maintain the sustainability of the company through brand image, price, and product quality on Roti Zouka Bakery in Margaasih District, Bandung Regency. The respondents of this research were 150 consumers who were taken by convenience sampling. The data was accumulated using a survey and was examined by employing the SPSS application. The results of this study shows that consumers’ perceptions of the brand affect repurchase intentions. This implies the positive impact of brand image on repurchase intention. Price also shown to have a significant effect on the repurchase decision. Therefore, it can be said that if the price is perceived as good, it will encourage consumers to buy bread at the Bakery. In addition, product quality, or in this case food quality, has a significant influence on repurchase intention at Zouka Bakery. Furthermore, the variable holds the greatest impact on the repurchase intention.